Empresas Responsáveis e Comunidades Cidadãs: Responsabilidade Social sob o Crivo da Comunicação Pública - BRITO, Walderes Lima de (2009)
The communication between companies and communities can be a tool to the strengthening of citizenship and a way to prove the social responsibility of an economical organization. The possibilities and limits of this process are the theme of this study and the research refers to the relationship between Petrobras and the population of Jardim Nova Goiânia, a neighborhood in Senador Canedo, GO which stands between two pipelines. During the research, local residents and leaders of the community were elected to work as interlocutors and were interviewed about their memories and points of view concerning how the neighborhood was populated, the infrastructure and their perception about the interaction between the company and the local residents. The investigation showed evidence that there were processes of institution of active citizenship, such as social practices that were not meant to make the residents dependent on them and the respect to the right of these residents to information. Those social practices were present in the mobilization and organization of the local residents and Petrobras contributed to this process. On the other hand, the research indicated the lack of evidence of the company s contribution to the sustainable development of the community which is still fragile in relation to the ability of acting as an association what would make the community capable of demanding moral responsibility from public systemic structures.